Steering Proton Migration in Hydrocarbons Using Intense Few-Cycle Laser Fields - Kübel, M.; Siemering, R.; Burger, C.; Kling, Nora G.; Li, H.; Alnaser, A. S.; Bergues, B.; Zherebtsov, S.; Azzeer, A. M.; Ben-Itzhak, I.; Moshammer, R.; de Vivie-Riedle, R.; et al. (My University, 2016)
Proton migration is a ubiquitous process in chemical reactions related to biology, combustion, and catalysis. Thus, the ability to manipulate the movement of nuclei with tailored light within a hydrocarbon molecule holds promise for far-reaching applications. Here, we demonstrate the steering of hydrogen migration in simple hydrocarbons, namely, acetylene and allene, using waveform-controlled, few-cycle laser pulses. The rearrangement dynamics is monitored using coincident 3D momentum imaging spectroscopy and described with a widely applicable quantum-dynamical model. Our observations reveal that the underlying control mechanism is due to the manipulation of the phases in a vibrational wave packet by the intense off-resonant laser field.